Green Banking In Sharia Banking: Initiation And Implementation Review - M. Johari, Sobar; Al-Qurratun Ainiyah, Dhina (International Journal of Science, Technology & Management, 2025)
This study aims to determine the initiation and implementation of green banking in relation to the influence of social, environmental, economic, human resources (HR), and ethics, on the initiation and implementation of green banking. This study was conducted by analyzing the results of interviews and questionnaires with 66 policy actors in Islamic banking in Islamic banking in the DIY Province. This study was analyzed using a descriptive quantitative method, in testing the hypothesis using multiple regression. The results of the study indicate that the highest initiation and implementation of green banking in Islamic banking in the Special Region of Yogyakarta (DIY) Province is in the economic aspect, this allows the implementation to still consider the profit and loss aspects in its implementation. While in the HR aspect it is the lowest, so it is still difficult to develop the totality of implementation and become serious homework for Islamic banking in Indonesia.